Fast and stable numerical method for neuronal modelling - Hashemi, Soheil; Abdolali, Ali (Communications in nonlinear science & numerical simulation, 2016)
•High accuracy and fast method for solving partial differential equations (PDE) of nonlinear equation of neural simulations.•Accuracy means more accurate simulations and therefore better device designing.•Complex structures with high number of meshes can be simulated by proposed method due to speed and stability of the method. Excitable cell modelling is of a prime interest in predicting and targeting neural activity. Two main limits in solving related equations are speed and stability of numerical method. Since there is a tradeoff between accuracy and speed, most previously presented methods for solving partial differential equations (PDE) are focused on one side. More speed means more accurate simulations and therefore better device designing. By considering the variables in finite differenced equation in proper time and calculating the unknowns in the specific sequence, a fast, stable and accurate method is introduced in this paper for solving neural partial differential equations. Propagation of action potential in giant axon is studied by proposed method and traditional methods. Speed, consistency and stability of the methods are compared and discussed. The proposed method is as fast as forward methods and as stable as backward methods. Forward methods are known as fastest methods and backward methods are stable in any circumstances. Complex structures can be simulated by proposed method due to speed and stability of the method.